2016
DOI: 10.1080/23273798.2016.1242761
|View full text |Cite
|
Sign up to set email alerts
|

How robust are prediction effects in language comprehension? Failure to replicate article-elicited N400 effects

Abstract: Current psycholinguistic theory proffers prediction as a central, explanatory mechanism in language processing. However, widely-replicated prediction effects may not mean that prediction is necessary in language processing. As a case in point, C. D. Martin et al. [2013. Bilinguals reading in their second language do not predict upcoming words as native readers do. Journal of Memory and Language, 69(4), 574-588. doi:10.1016/j.jml.2013.08.001] reported ERP evidence for prediction in native-but not in non-native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 32 publications
5
71
4
Order By: Relevance
“…Based on the results reported in Ito, Martin, et al (2016a) and on the additional observations presented in this rebuttal, we conclude that our study is a failure of conceptual replication of Martin et al (2013), and, by extension, of DeLong et al Alternatively, this effect is so small it could not be reliably detected in our replication attempts. Even if a small effect were real, but difficult to detect because of its size, one could question whether such an effect should be regarded as stalwart evidence that people probabilistically pre-activate phonological information and that this activation plays a meaningful role in everyday language comprehension.…”
Section: Resultscontrasting
confidence: 36%
See 1 more Smart Citation
“…Based on the results reported in Ito, Martin, et al (2016a) and on the additional observations presented in this rebuttal, we conclude that our study is a failure of conceptual replication of Martin et al (2013), and, by extension, of DeLong et al Alternatively, this effect is so small it could not be reliably detected in our replication attempts. Even if a small effect were real, but difficult to detect because of its size, one could question whether such an effect should be regarded as stalwart evidence that people probabilistically pre-activate phonological information and that this activation plays a meaningful role in everyday language comprehension.…”
Section: Resultscontrasting
confidence: 36%
“…Failure to replicate article-elicited N400 effects" (Ito, Martin, & Nieuwland, 2016a), we report two experiments which failed to replicate existing ERP evidence for prediction as reported in C. D. Martin et al (2013), whose study resembled DeLong, Urbach, and from hereon DUK05). DeLong, Urbach, and Kutas (2017; from hereon, DUK17) recently published a commentary which depicts our publication as a case of poor scholarship that makes "no substantive contribution to the literature on what factors may matter for prediction and when."…”
mentioning
confidence: 71%
“…Support for word form preactivation also comes from other studies using the a/an paradigm. For instance, Martin et al (), a study based on DeLong et al (), similarly observed an a/an article N400 prediction effect, albeit at a slower presentation rate (700‐ms SOA, as confirmed in Ito, Martin, & Nieuwland, ). Ito, Martin, and Nieuwland likewise obtained a marginally significant ( p = 0.06) prediction N400 effect at a/an articles for native English‐speaking participants (see discussion in DeLong, Urbach, & Kutas, ).…”
Section: Introductionmentioning
confidence: 77%
“…From a Bayesian perspective, however, processing that is not strictly anticipatory (i.e., where prior knowledge modulates processing of a word as it is being heard) is still predictive (Norris et al, 2016). There is also debate about whether prediction is the sole process underlying language comprehension, or whether it is only one of multiple processes (Huettig & Mani, 2016;Ito, Martin, & Nieuwland, 2017). Relatedly, there is current discussion about whether a key demonstration of prediction replicates (DeLong et al, 2005;Ito et al, 2017;Nieuwland et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is also debate about whether prediction is the sole process underlying language comprehension, or whether it is only one of multiple processes (Huettig & Mani, 2016;Ito, Martin, & Nieuwland, 2017). Relatedly, there is current discussion about whether a key demonstration of prediction replicates (DeLong et al, 2005;Ito et al, 2017;Nieuwland et al, 2018). In spite of these ongoing debates, there is consensus that, at least under some circumstances (e.g.…”
Section: Introductionmentioning
confidence: 99%